2020
DOI: 10.1016/j.seizure.2019.12.002
|View full text |Cite
|
Sign up to set email alerts
|

New-onset refractory status epilepticus: A retrospective cohort study

Abstract: To describe the clinical, laboratory, neuroimaging, electroencephalographic features, etiology, treatment, as well as short-term and long-term outcomes of adults with new-onset refractory status epilepticus (NORSE). Method: A retrospective, single institution cohort study (2010)(2011)(2012)(2013)(2014)(2015)(2016)(2017)(2018) of consecutive adult patients with NORSE. Results: Among 20 patients with NORSE, nine (45 %) had prodromal febrile illness, 12 (60 %) had evidence of inflammation on CSF profile. Six pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
43
1
10

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(60 citation statements)
references
References 20 publications
6
43
1
10
Order By: Relevance
“…This retrospective long‐term follow‐up MRI study evaluated the timeline of MRI abnormalities in adult NORSE patients. The percentage of MRI abnormalities in NORSE patients in our study (82%) and other, previous studies (62%‐100%), 2,6–10 was higher than in the general population of SE patients (25%) 11 …”
Section: Discussionsupporting
confidence: 44%
See 1 more Smart Citation
“…This retrospective long‐term follow‐up MRI study evaluated the timeline of MRI abnormalities in adult NORSE patients. The percentage of MRI abnormalities in NORSE patients in our study (82%) and other, previous studies (62%‐100%), 2,6–10 was higher than in the general population of SE patients (25%) 11 …”
Section: Discussionsupporting
confidence: 44%
“…This study demonstrated initial diffuse leptomeningeal enhancement in 43% of NORSE patients, which was higher than in previous studies (6%‐25%) 2,8–10 . The higher percentage can be explained by our different method for calculating the percentage, which used the number of contrast‐enhanced MRIs performed within 16 days of seizure onset, not just the total number of MRIs without consideration for the use of contrast enhancement or the time at which the MRI was performed after seizure onset, as has been described in previous studies.…”
Section: Discussionmentioning
confidence: 50%
“…5 One might argue that C-NORSE is an epileptic syndrome and should not be confused with AE; randomized controlled trial with immunotherapy has not been conducted yet; therefore, little information is available on the adequate dosage of other immune treatments to formulate any recommendation. 3 However, it is not easy in clinical practice to exclude a possibility of C-NORSE or antibody-positive AE particularly at the early stage of SE before antibody test results become available; therefore, many patients with NORSE may have been treated with immunotherapy, 5 , 26 although the first-line immunotherapy is presumed to be less effective. However, if the C-NORSE score is high (≥5) on referral from other hospital, it is suggested that the patient is more likely to be negative for neuronal antibodies, thus more likely to be less responsive to first-line immunotherapy and have poor outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Ketamine, a nonselective and noncompetitive antagonist of NMDAR, blocks the influx of Ca 2+ and Na + by binding to relevant sites inside the ion channel of the NMDAR and consequently inhibiting the transmission of excitatory nerve impulses [7][8][9][10][11]. To understand the efficacy and safety of ketamine in patients with RSE and SRSE, Hofler et al [12] analyzed data from 42 RSE or SRSE patients, and the results showed that 64% of the patients achieved resolution of SE with no adverse events.…”
Section: Ketamine In Refractory Status Epilepticusmentioning
confidence: 99%
“…In recent years, ketamine has gradually been used in RSE patients with special etiologies and has achieved good outcomes [7,8]. Anti-NMDAR encephalitis is an autoimmune disease related to the production of antibodies to the NR1 and NR2 subunits of the NMDARs.…”
Section: Ketamine In Refractory Status Epilepticusmentioning
confidence: 99%